Bank Marketing and Its Effects on Customer Retention in Microfinance in Yaounde, Cameroon - Grimbald, Ndah; Chelsea Mah, Tarbot (Business and Economic Research, 2023)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">This study seeks to assess bank marketing and its impact on customer retention in microfinance in Yaoundé, Cameroon. A cross-sectional research design consisting of 348 clients of category two microfinances were sampled from the center region of Cameroon. Data for the study was sourced using closed structured questionnaires. The analysis was concluded using statistical software’s such as Statistical Package for Social Sciences (SPSS 24) and Analysis of Moment Structures (AMOS24). The results from the analysis reveal that Customer service and retention have a significant positive impact on customer retention. The study therefore concluded that emphasis on better customer services leads to a high customer retention rate in category two microfinances in Yaounde, Cameroon. A new model called Bank Marketing and Customer retention Model (BMCR Model) was developed to test the relationship amongst variables. This study contributes to the limited theoretical and empirical evidence of the impact of bank marketing on customer retention in microfinances in Yaounde, Cameroon.